2022
DOI: 10.3389/fnut.2022.813202
|View full text |Cite
|
Sign up to set email alerts
|

Drinking Natural Mineral Water Maintains Bone Health in Young Rats With Metabolic Acidosis

Abstract: IntroductionMetabolic acidosis affects bone health. It remains unclear whether drinking natural mineral water is better for maintaining bone health in the youth with metabolic acidosis.Materials and MethodsSixty young female rats (3-weeks-old) were randomly divided into three groups and drank purified water (PW, as control), bicarbonate-rich natural mineral water (Bic-NMW), or sulfate-rich natural mineral water (Sul-NMW), which, respectively, contained calcium (0.17, 155, and 175 mg/L), bicarbonate (0.1360, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 41 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…Previous studies have reported the beneficial effects of drinking mineral water on human health ( 14 17 ). However, whether drinking natural mineral water can prevent obesity caused by metabolic disease such as hyperuricemia has not been reported, particularly from the perspective of metabolic levels and gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported the beneficial effects of drinking mineral water on human health ( 14 17 ). However, whether drinking natural mineral water can prevent obesity caused by metabolic disease such as hyperuricemia has not been reported, particularly from the perspective of metabolic levels and gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…The characteristics of the C-cell mineral water are displayed in Table 1. 17 O-NMR half peak width is 70.77 MHz for general water, and 48.58 MHz for the small molecule C-cell mineral water (Figures 1A,B).…”
Section: Characteristics Of the C-cell Mineral Watermentioning
confidence: 99%
“…A study conducted on rats demonstrated that those receiving mineral water high in calcium had a higher bone mineral density compared to those who did not receive this mineral water. While human studies are more complex, this does suggest potential benefits for bone health [ 75 ]. Additionally, some studies have considered the benefits of calcium-rich mineral water for individuals who have difficulty consuming traditional calcium sources.…”
Section: Impact On Bone Healthmentioning
confidence: 99%
“…Animal studies also proved that the consumption of low mineral water leads to a higher risk of cardiovascular disease [16] and impaired bone quality [18]. Meanwhile, the consumption of natural mineral water may contribute to controlling blood lipid and glucose levels [19], improving glycemic control [20], and maintaining bone health in young rats with metabolic acidosis [21].…”
Section: Introductionmentioning
confidence: 99%